Animal multicellularity and polarity without Wnt signaling - Schenkelaars, Q.; Pratlong, M.; Kodjabachian, L.; Fierro-Constain, L.; Vacelet, J.; Le Bivic, A.; Renard, E.; Borchiellini, C. (Scientific Reports, 2017)
Acquisition of multicellularity is a central event in the evolution of Eukaryota. Strikingly, animal multicellularity coincides with the emergence of three intercellular communication pathways – Notch, TGF-ß and Wnt – all considered as hallmarks of metazoan development. By investigating Oopsacas minuta and Aphrocallistes vastus, we show here that the emergence of a syncytium and plugged junctions in glass sponges coincides with the loss of essential components of the Wnt signaling (i.e. Wntless, Wnt ligands and Disheveled), whereas core components of the TGF-ß and Notch modules appear unaffected. This suggests that Wnt signaling is not essential for cell differentiation, polarity and morphogenesis in glass sponges. Beyond providing a comparative study of key developmental toolkits, we define here the first case of a metazoan phylum that maintained a level of complexity similar to its relatives despite molecular degeneration of Wnt pathways